DISPENSASI PERNIKAHAN BEDA AGAMA MENURUT PERSPEKTIF MAZHAB - Oktavia, Elysa Nur; Kamilah, Mutiara; Resti, Nurinda; Ummah, Siti Roiyyatul (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2023)
This journal reviews the Dispensation of Interfaith Marriage in the Perspective of Schools. This research aims to minimize the occurrence of interfaith marriages, so that we as human beings strengthen our faith in religion, and so that we know that interfaith marriages were not agreed upon by the four Imams of the Madhhab and there is no dispensation.This research is qualitative, while the research instrument is interviews and is based on sources from trusted journals and books. The data source for this research is an interview with one of the heads of the School Comparative Study Program who is also a Lecturer for the Ushul Fiqh course, namely Mrs. Siti Hana, M.A, who talks about the mafsada of interfaith marriage. He said that marriage is like the ship's boat, so the captain and passengers must have the same goal, the same goes for marriage, if the husband and wife have differences of opinion, there will be inequality until something causes a divorce. And if the couple has children, he will be confused with two choices between following the religion professed by his father or by his mother. Because religion is not just a status but a handle for our daily lives. That was conveyed by Ms. Siti Hana, M.A as head of the Comparative Study Program. Likewise, the four Imams of the Madhhab did not agree with the marriage of different religions and that is illegal. If the marriage is illegal, then all the relationships that the couple does include adultery.